Ternary PdNi-based nanocrystals supported on nitrogen-doped reduced graphene oxide as highly active electrocatalysts for the oxygen reduction reaction. (1st May 2017) - Sun, Lingna; Liao, Biyan; Ren, Xiangzhong; Li, Yongliang; Zhang, Peixin; Deng, Libo; Gao, Yuan
Abstract: Ternary PdNiM (M = Cu or Sn) alloys are supported on nitrogen-doped graphene (NG) by a simple chemical reduction method. PdNiM (M = Cu or Sn) are used as nanocatalysts for the oxygen reduction reaction (ORR) in an alkaline electrolyte. The nanocatalysts are characterized by scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The physical properties demonstrate that PdNiM (M = Cu or Sn) nanoparticles are highly alloyed and well dispersed on NG. PdNiM (M = Cu or Sn) electrocatalysts exhibit high ORR activity and stability, which are better than 20% commercial Pd black and close to 20% commercial Pt/C. These results indicate that the addition of Sn or Cu into a PdNi-based catalyst not only reduces the level of Pd but also greatly improves the catalytic activity.